THE DESCRIPTION OF WRITING STRATEGY, SELF-EFFICACY, AND WRITING ANXIETY RELATING TO WRITING PERFORMANCE - Lelly Suhartini; Samdin Samdin; La Ode Nggawu; Aris Badara; Putri Tipa Anasi; Andri Estining Sejati (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Academic writing in English remains a persistent challenge for English as a Foreign Language (EFL) students, whose written work often fails to meet disciplinary expectations due to complex interactions among linguistic competence, psychological states, and strategic behavior. While previous quantitative research, particularly studies employing Structural Equation Modeling (SEM), has examined causal and mediating relationships among writing self-efficacy, anxiety, strategy use, and performance, these approaches offer limited insight into how these constructs manifest in students' lived experiences and writing processes. To address this gap, the present study adopts a descriptive qualitative approach to portray the characteristics, expressions, and interconnections of writing strategy use, self-efficacy beliefs, and writing anxiety as experienced by EFL learners in relation to their academic writing performance. In-depth semi-structured interviews and analysis of writing artifacts were conducted with 18 purposively selected students from the 4th, 6th, and 8th semesters of the English Language Education Study Program at Halu Oleo University. Data were analyzed through iterative thematic analysis to generate rich descriptions of participants' strategic behaviors, confidence levels, emotional responses, and perceived writing outcomes. The findings depict self-efficacious students as actively employing planning, drafting, and revising strategies with metacognitive awareness, which they associate with improved text quality and fluency. In contrast, students with low self-efficacy frequently reported strategy avoidance or mechanical application of techniques without adaptation to task demands. Writing anxiety emerged not as a uniform barrier but as a context-dependent experience, sometimes coexisting with strategic effort yet often disrupting cognitive resources during high-stakes writing tasks. Notably, the descriptive accounts reveal that strategy use appears closely intertwined with self-efficacy beliefs, while anxiety manifests more independently without consistent patterns of strategic compensation. These qualitative descriptions complement prior SEM-based findings by illuminating the experiential dimensions underlying statistical relationships, highlighting the need for pedagogy that nurtures self-efficacy through mastery experiences, cultivates flexible strategy repertoires with explicit modeling, and addresses anxiety through supportive writing environments. The study contributes a nuanced understanding of the psychological and strategic landscape of EFL academic writing beyond what variable-centered quantitative approaches alone can capture.